Reversible photochromic apatite material with color center moving behavior as well as preparation method and application of reversible photochromic apatite material

By changing the basic synthetic components of apatite material and using NaCl flux combined with microwave method and molten salt method, reversible photochromic apatite material with color heart movement behavior was prepared, which solved the photogenesis of apatite material The problem of insufficient color change effect has achieved multi-color anti-counterfeiting application, which improves security and cracking difficulty.

CN119505861APending Publication Date: 2025-02-25JIANGNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411709955.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The application of apatite materials in the field of photochromicity is limited by insufficient color changes, low sensitivity to visible light, and a large impact on environmental humidity and temperature. Doping rare earth ions or transition metal ions is complex and costly. .

Method used

By changing the basic synthetic components of apatite material, using NaCl as a flux, combining microwave method with molten salt method, reversible photochromic apatite material with color center movement behavior is prepared, achieving multi-color anti-counterfeiting application .

Benefits of technology

Apatite material with better photochromic performance and more uniform particles was obtained, and multi-color anti-counterfeiting labels were realized, meeting the society's needs for anti-counterfeiting and information encryption, and improving security and cracking difficulties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505861A_ABST
    Figure CN119505861A_ABST
Patent Text Reader

Abstract

The invention provides a reversible photochromic apatite material with a color center moving behavior and a preparation method and application thereof, the chemical expression is Sr5 (PO4) 3F1-yCly: x% Eu, x = 0-4; y = 0-1; the preparation method comprises the following steps: (1) weighing reactants SrCO3, SrF2, SrCl2 and (NH4) 2HPO4 according to the molar percentage of 9: 1-y: y: 6, and adding x% of Eu2O3; (2) adding a fluxing agent NaCl and absolute ethyl alcohol, and mixing to obtain a reaction mixture; (3) putting the reaction mixture into a sample crucible, covering the sample crucible with a crucible cover, putting the sample crucible into a microwave receiving device, putting the microwave receiving device into a heat-insulating brick, and putting the heat-insulating brick into a microwave reaction furnace; and (4) setting reaction power and time for synthesis, washing and drying to obtain the apatite material. NaCl is used as a fluxing agent, a microwave method and a molten salt method are combined, the reversible photochromic apatite material which is better in photochromic performance, more uniform in particle and has a color center moving behavior is prepared, and multicolor anti-counterfeiting application is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic photochromic materials, and in particular to a reversible photochromic apatite material with color center migration behavior, a preparation method and an application thereof. Background Art

[0002] Photochromic materials are divided into organic photochromic materials and inorganic photochromic materials. Compared with organic photochromic materials, inorganic photochromic materials tend to have higher thermal stability, chemical stability and light stability. This makes them suitable for long-term applications and can be used normally even in harsh environments where organic materials may degrade. As a member of inorganic photochromic materials, apatite materials have always played a vital role in the development of optical functional materials, but their application in the field of photochromism is still subject to some limitations and challenges. First, compared with other inorganic photochromic materials (such as oxides or transition metal compounds), the photochromic effect of apatite materials may not be significant enough, the color change is not obvious enough or the sensitivity to visible light is low. This makes their visual effects relatively weak in practical applications. Secondly, the photochromic performance may be affected by environmental humidity, temperature and other conditions, showing instability, especially in humid or high temperature environments, which may affect its photochromic effect. Finally, in order to improve the photochromic performance, it is usually necessary to dope rare earth ions or transition metal ions into the apatite structure, but the selection of suitable dopants is limited and the doping process is complicated, which affects the preparation cost and batch consistency of the material.

[0003] In the application of photochromic materials, anti-counterfeiting is a hot topic. Currently, existing research focuses more on the application of single photochromic color to achieve anti-counterfeiting security. However, a single anti-counterfeiting color cannot meet the needs of most people in terms of security and diversity. Summary of the invention

[0004] The present invention provides a reversible photochromic apatite material with color center migration behavior and a preparation method and application thereof to solve the above problems.

[0005] The purpose of the present invention is to provide a reversible photochromic apatite material with color center migration behavior, the chemical formula of which is: Sr5(PO4)3F 1-y Cl y :x%Eu, where x=0~4; y=0~1.

[0006] Another object of the present invention is to provide a method for preparing a reversible photochromic apatite material having color center migration behavior, comprising the following steps:

[0007] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x ranges from 0 to 4 and y ranges from 0 to 1, to obtain a mixture and transfer it into a mortar;

[0008] Step (ii), adding 0.1-1 g of a flux NaCl per 0.5 g of the mixture in a mortar, and then adding 2-6 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0009] Step (iii), first, prepare a microwave receiving device, the microwave receiving device is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the activated carbon particles act as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity ratio of the carbon powder crucible to the sample crucible is 9:1, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of the aluminosilicate insulation brick with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0010] Step (iv), setting the power of the microwave reaction furnace to 800-1000W, the time to synthesize for 15-30min, after the reaction is completed in a high-temperature reducing atmosphere, washing with alcohol and drying to obtain the reversible photochromic apatite material with color center migration behavior.

[0011] As a further preference of the above scheme:

[0012] In the step (ii), 0.5 g of the flux NaCl is added to every 0.5 g of the mixed material, and 4 ml of anhydrous ethanol is mixed with every 0.5 g of the mixed material, and a dry and uniformly mixed reaction mixture is obtained after grinding.

[0013] As a further preference of the above scheme:

[0014] In the step (iii), the mass of activated carbon particles required for every 0.5 g of reaction mixture is 11 to 15 g.

[0015] As a further preference of the above scheme:

[0016] In the step (iv), the power of the microwave reaction furnace is 1000 W and the microwave time is 25 min.

[0017] Another object of the present invention is to provide an application of a reversible photochromic apatite material with color center migration behavior, wherein the apatite material is applied to an anti-counterfeiting label: the apatite material is ground to obtain a powder sample with uniform particles, the prepared powder sample is combined with a pattern template, and a multi-color anti-counterfeiting label that changes color with ultraviolet light is obtained.

[0018] Beneficial effects of the present invention: The present invention uses NaCl as a flux, combines the microwave method with the molten salt method, prepares a reversible photochromic apatite material with better photochromic performance and more uniform particles and color center migration behavior, and realizes multi-color anti-counterfeiting applications, as follows:

[0019] (1) Compared with the prior art that changes the properties of apatite materials by doping and modification, the technical solution of the present invention optimizes the apatite materials by changing their basic synthetic components, and provides a photochromic material with color center migration behavior to meet the social needs for security and diversity in anti-counterfeiting and information encryption;

[0020] (2) The present invention uses microwave-assisted molten salt method, uses salt as flux, combines microwave method with molten salt method, and based on the high thermal stability of molten salt and the free movement characteristics of ions in the melt, makes the reactants react evenly in the liquid phase environment, and the synthesis is more uniform. Combined with the simple, fast and energy-saving characteristics of microwave method, apatite materials with high purity and excellent photochromic properties are synthesized, getting rid of the complex and time-consuming experimental process of traditional high-temperature solid phase method and hydrothermal method;

[0021] (3) By doping with different contents of europium ions, the apatite material is endowed with the ability of photochromism. By gradually replacing fluorine ions with chloride ions, the effects of different fluorine and chlorine contents on the photochromic properties of the apatite material are studied. By regularly changing the ratio of fluorine and chlorine contents, the photochromic properties are regulated and controlled, and the shift of visible light absorbance after photochromism is achieved, thus realizing a multi-color, fast color change efficiency, high color change contrast and color center shift behavior photochromic apatite material;

[0022] (4) The reversible photochromic apatite material with color center migration behavior obtained by the preparation method of the present invention can also be used in anti-counterfeiting labels. By combining the prepared powder sample with a pattern template, an anti-counterfeiting label that changes color with ultraviolet light is produced, which can meet most simple anti-counterfeiting needs and some complex pattern anti-counterfeiting needs with high requirements. Because this material has a visible light absorbance that is red-shifted after photochromism, the change from purple to green and then to blue is achieved through the substitution of chloride ions. Therefore, multi-color anti-counterfeiting with higher security can be achieved in anti-counterfeiting applications. Because it has a variety of colors, the anti-counterfeiting pattern can choose a more complex and multi-color pattern to meet the needs of anti-counterfeiting encryption, such as a complex butterfly pattern, which can better highlight the advantages brought by the polychromaticity of this material, not only meeting the color requirements, but also greatly improving security and cracking difficulty. In addition, the colored pattern can gradually fade over time and can also be accelerated by long-wavelength light irradiation to accelerate its fading, thereby improving its concealment and realizing an application in multi-color encryption anti-counterfeiting. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0024] Figure 1 It is an XRD standard diffraction card and an X-ray diffraction spectrum of the materials prepared in Examples 1 to 4 of the present invention;

[0025] Figure 2 is a graph showing the change in reflectivity of the materials prepared in Examples 1 to 4 of the present invention before and after irradiation with a 254nm ultraviolet lamp;

[0026] Figure 3 It is the XRD standard diffraction card and the X-ray diffraction spectra of the materials prepared in Examples 11 and 13-17 of the present invention;

[0027] Figure 4 is a photochromic photograph of the materials prepared in Examples 11 and 13-17 of the present invention after irradiation with a 254nm ultraviolet lamp;

[0028] Figure 5 is a comparison chart of the reflectivity difference of the materials prepared in Examples 11 and 13-17 of the present invention before and after irradiation with a 254nm ultraviolet lamp;

[0029] Figure 6 It is the XRD standard diffraction card and the X-ray diffraction spectra of the materials prepared in Example 5 and Examples 18-22 of the present invention;

[0030] Figure 7 are reflectance spectra and photochromic photographs of the materials prepared in Examples 11, 20 and 22 of the present invention before and after irradiation with a 254 nm ultraviolet lamp;

[0031] Figure 8 It is a comparison diagram of the normalized reflectivity difference of the materials prepared in Examples 11 and 18-22 of the present invention before and after irradiation with a 254nm ultraviolet lamp;

[0032] Fig. 9 is a bar graph comparing the areas of the materials prepared in Examples 11 and 18-22 of the present invention before and after photochromism in the range of 300nm-800nm;

[0033] Fig.10 is a SEM-EDS image of the material prepared in Example 20 of the present invention;

[0034] Fig.11 This is a photochromic cyclic test graph of the material prepared in Example 20 of the present invention;

[0035] Fig.12 It is an anti-counterfeit label obtained by using a pattern template from the materials prepared in Examples 11, 20 and 22 of the present invention;

[0036] Fig.13 The diffuse reflectance spectra of Example 11 of the present invention in which NaCl is added and the comparative example 1 in which NaCl is not added, and the photos before and after photochromism. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. The experimental device used in the embodiments of the present invention includes a microwave reactor and a microwave receiving device. The assembled microwave receiving device is insulated with insulation bricks and then placed in the microwave reactor for reaction. The carbon powder of the microwave receiving device acts as a receiver of electromagnetic waves to generate high temperature and reducing atmosphere to enable the sample to be synthesized simply and quickly.

[0038] Example 1

[0039] The reversible photochromic apatite material with color center migration behavior provided in this embodiment 1 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0040] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0041] Step (ii), adding 0.1 g of a flux NaCl to every 0.5 g of the mixture in a mortar, and then adding 2 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0042] Step (three)

[0043] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0044] Step (iv), setting the power of the microwave reactor to 1000 W and the time to 15 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere. After the reaction, the obtained product is rinsed with alcohol 5 times to remove excess NaCl impurities, and dried in an oven at 60°C for 1 h to obtain the reversible photochromic apatite material with color center migration behavior, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0045] Example 2

[0046] The reversible photochromic apatite material with color center migration behavior provided in this embodiment 2 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0047] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0048] Step (ii), adding 0.1 g of a flux NaCl to every 0.5 g of the mixture in a mortar, and then adding 2 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0049] Step (three)

[0050] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0051] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 20 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 50°C for 1.5 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0052] Example 3

[0053] The reversible photochromic apatite material with color center migration behavior provided in this embodiment 3 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0054] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0055] Step (ii), adding 0.1 g of a flux NaCl to every 0.5 g of the mixture in a mortar, and then adding 2 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0056] Step (three)

[0057] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0058] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 3 times with alcohol to remove excess NaCl impurities, and dried in an oven at 70°C for 0.5 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0059] Example 4

[0060] The reversible photochromic apatite material with color center migration behavior provided in this embodiment 4 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0061] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0062] Step (ii), adding 0.1 g of a flux NaCl to every 0.5 g of the mixture in a mortar, and then adding 2 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0063] Step (three)

[0064] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0065] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 30 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed with alcohol 6 times to remove excess NaCl impurities, and dried in an oven at 40°C for 2 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0066] Example 5

[0067] The reversible photochromic apatite material with color center migration behavior provided in this embodiment 5 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0068] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0069] Step (ii), adding 0.1 g of a flux NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0070] Step (three)

[0071] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0072] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 65°C for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0073] Example 6

[0074] The reversible photochromic apatite material with color center migration behavior provided in Example 6 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0075] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0076] Step (ii), adding 0.1 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 6 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0077] Step (three)

[0078] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0079] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 3 times with alcohol to remove excess NaCl impurities, and dried in an oven at 55°C for 1.5 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0080] Example 7

[0081] The reversible photochromic apatite material with color center migration behavior provided in this embodiment 7 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0082] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0083] Step (ii), adding 0.1 g of a flux NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0084] Step (three)

[0085] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 11 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0086] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 65°C for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0087] Example 8

[0088] The reversible photochromic apatite material with color center migration behavior provided in Example 8 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0089] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0090] Step (ii), adding 0.1 g of a flux NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0091] Step (three)

[0092] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 15 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0093] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 8 times with alcohol to remove excess NaCl impurities, and dried in an oven at 70°C for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0094] Example 9

[0095] The reversible photochromic apatite material with color center migration behavior provided in Example 9 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0096] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0097] Step (ii), adding 0.1 g of a flux NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0098] Step (three)

[0099] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 15 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0100] Step (iv), setting the power of the microwave reactor to 800 W and the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere. After the reaction, the obtained product is rinsed with alcohol 5 times to remove excess NaCl impurities, and dried in an oven at 70°C for 1 h to obtain the reversible photochromic apatite material with color center migration behavior, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0101] Example 10

[0102] The reversible photochromic apatite material with color center migration behavior provided in this embodiment 10 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0103] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0104] Step (ii), adding 0.1 g of a flux NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0105] Step (three)

[0106] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 15 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0107] Step (iv), setting the power of the microwave reactor to 900 W and the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere. After the reaction, the obtained product is rinsed with alcohol 5 times to remove excess NaCl impurities, and dried in an oven at 70°C for 1 h to obtain the reversible photochromic apatite material with color center migration behavior, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0108] Embodiment 11

[0109] The reversible photochromic apatite material with color center migration behavior provided in this embodiment 11 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0110] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0111] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0112] Step (three)

[0113] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0114] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 65°C for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0115] Example 12

[0116] The reversible photochromic apatite material with color center migration behavior provided in Example 12 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0117] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0, to obtain a mixture and transfer it into a mortar;

[0118] Step (ii), adding 1 g of flux NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0119] Step (three)

[0120] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0121] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 65°C for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:1%Eu.

[0122] Embodiment 13

[0123] The reversible photochromic apatite material with color center migration behavior provided in Example 13 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0124] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 0 and y is 0, to obtain a mixture and transferring it into a mortar;

[0125] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0126] Step (three)

[0127] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0128] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 65° C. for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula is: Sr5(PO4)3F.

[0129] Embodiment 14

[0130] The reversible photochromic apatite material with color center migration behavior provided in Example 14 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0131] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 0.5 and y is 0, to obtain a mixture and transfer it into a mortar;

[0132] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0133] Step (three)

[0134] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0135] Step (iv), setting the power of the microwave reactor to 1000 W, the time to synthesize for 25 min, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 65°C for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:0.5%Eu.

[0136] Embodiment 15

[0137] The reversible photochromic apatite material with color center migration behavior provided in Example 15 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0138] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1.5 and y is 0, to obtain a mixture and transfer it into a mortar;

[0139] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0140] Step (three)

[0141] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0142] Step (iv), setting the power of the microwave reactor to 1000 W, the time to synthesize for 25 min, the reaction mixture reacts in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 65°C for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:1.5%Eu.

[0143] Example 16

[0144] The reversible photochromic apatite material with color center migration behavior provided in Example 16 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0145] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 2 and y is 0, to obtain a mixture and transferring it into a mortar;

[0146] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0147] Step (three)

[0148] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0149] Step (iv), setting the power of the microwave reactor to 1000 W, the time to synthesize for 25 min, the reaction mixture reacts in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 65°C for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:2%Eu.

[0150] Embodiment 17

[0151] The reversible photochromic apatite material with color center migration behavior provided in Example 17 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0152] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 4 and y is 0, to obtain a mixture and transferring it into a mortar;

[0153] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0154] Step (three)

[0155] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0156] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 65°C for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F:4%Eu.

[0157] Embodiment 18

[0158] The reversible photochromic apatite material with color center migration behavior provided in Example 18 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0159] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0.2, to obtain a mixture and transfer it into a mortar;

[0160] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0161] Step (three)

[0162] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0163] Step (iv), setting the power of the microwave reaction furnace to 1000W, the time to synthesize for 25min, the reaction mixture is reacted in a high temperature reducing atmosphere, after which the obtained product is rinsed with alcohol 4 times to remove excess NaCl impurities, and dried in an oven at 65°C for 1h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F 0.8 Cl 0.2 :1%Eu.

[0164] Embodiment 19

[0165] The reversible photochromic apatite material with color center migration behavior provided in Example 19 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0166] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0.4, to obtain a mixture and transfer it into a mortar;

[0167] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0168] Step (three)

[0169] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0170] Step (iv), setting the power of the microwave reaction furnace to 1000W, the time to synthesize for 25min, the reaction mixture is reacted in a high temperature reducing atmosphere, after which the obtained product is rinsed with alcohol 4 times to remove excess NaCl impurities, and dried in an oven at 65°C for 1h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F 0.6 Cl 0.4 :1%Eu.

[0171] Embodiment 20

[0172] A reversible photochromic apatite material with color center migration behavior provided in Example 20 has a chemical formula of Sr5(PO4)3F:1%Eu, and a preparation method includes the following steps:

[0173] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0.6, to obtain a mixture and transfer it into a mortar;

[0174] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0175] Step (three)

[0176] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0177] Step (iv), setting the power of the microwave reaction furnace to 1000W, the time to synthesize for 25min, the reaction mixture is reacted in a high temperature reducing atmosphere, after which the obtained product is rinsed with alcohol 4 times to remove excess NaCl impurities, and dried in an oven at 65°C for 1h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F 0.4 Cl 0.6 :1%Eu.

[0178] Embodiment 21

[0179] The reversible photochromic apatite material with color center migration behavior provided in Example 21 has a chemical formula of Sr5(PO4)3F:1%Eu, and a preparation method includes the following steps:

[0180] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 0.8, to obtain a mixture and transfer it into a mortar;

[0181] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0182] Step (three)

[0183] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0184] Step (iv), setting the power of the microwave reaction furnace to 1000W, the time to synthesize for 25min, the reaction mixture is reacted in a high temperature reducing atmosphere, after which the obtained product is rinsed with alcohol 4 times to remove excess NaCl impurities, and dried in an oven at 65°C for 1h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3F 0.2 Cl 0.8 :1%Eu.

[0185] Embodiment 22

[0186] The reversible photochromic apatite material with color center migration behavior provided in Example 22 has a chemical formula of Sr5(PO4)3F:1%Eu, and the preparation method includes the following steps:

[0187] Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x is 1 and y is 1, to obtain a mixture and transfer it into a mortar;

[0188] Step (ii), adding 0.5 g of a fluxing agent NaCl to every 0.5 g of the mixture in a mortar, and then adding 4 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture;

[0189] Step (three)

[0190] First, prepare a microwave receiving device, which is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the carbon powder crucible has a capacity of 45 ml, and the total mass of the activated carbon particles is 13 g. The activated carbon particles serve as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh 0.5 g of the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity of the sample crucible is 5 ml, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of aluminosilicate insulation bricks with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor;

[0191] Step (iv), setting the power of the microwave reactor to 1000 W, the time to 25 min for synthesis, the reaction mixture is reacted in a high-temperature reducing atmosphere, after which the product is rinsed 4 times with alcohol to remove excess NaCl impurities, and dried in an oven at 65°C for 1 h, and finally the reversible photochromic apatite material with color center migration behavior is obtained, the chemical formula of which is: Sr5(PO4)3Cl:1%Eu.

[0192] Embodiment 23

[0193] This Example 23 is based on any one of Examples 1 to 22. This Example 23 provides an application of a reversible photochromic apatite material with color center migration behavior, which is applied to multi-color anti-counterfeiting. Specifically: the obtained reversible photochromic apatite material with color center migration behavior is fully ground in a ceramic mortar to obtain a powder sample with uniform particles. The prepared powder sample is combined with a pattern template to obtain various anti-counterfeiting labels that change color with ultraviolet light, thereby realizing a more secure and reusable multi-color anti-counterfeiting application.

[0194] Comparative Example 1

[0195] In order to further verify that the sample obtained by the method of the present invention is more uniformly synthesized and has better photochromic properties, the difference between this comparative example 1 and the aforementioned embodiment 11 is that the flux NaCl is not added in step 2. Fig.13 By comparing Example 11 with Comparative Example 1, the Sr5(PO4)3Cl:1%Eu sample obtained in Example 11 confirms that the sample synthesized by the microwave molten salt method of the present invention has a higher reflectivity before discoloration, better photochromism after discoloration, and more uniform particles. The addition of NaCl does promote the exchange between ions, making the sample more evenly heated during the synthesis process.

[0196] Results Analysis

[0197] See also Figure 1 , Figure 1The XRD (X-ray diffraction) standard diffraction card PDF#01-072-5905 of Sr5(PO4)3F was used as a reference to verify the synthesis under the same conditions and different microwave times. The X-ray diffractometer was used to test and analyze the materials obtained in Examples 1-4. The results are as follows: Figure 1 As shown, the XRD data of the product is consistent with the standard diffraction card, indicating that the samples under different microwave times can be successfully synthesized. Then, the reflectivity of the materials obtained in Examples 1-4 before and after photochromism was measured by ultraviolet spectrometer, and the results are shown in FIG. Figure 2 As shown, the position of the maximum absorbance change is near 554nm, and the color of the sample is purple. Then, by comparing the difference in reflectivity, it is found that the material obtained in Example 3 is the sample with the best photochromic performance. Examples 3, 5 and 6 optimize the amount of anhydrous ethanol added during grinding. Through experiments, it is found that although all samples can be synthesized, the material particles obtained in Example 5 are more uniform. Similarly, the amount of carbon powder added was optimized by Examples 5, 7 and 8, and all the examples were successfully synthesized, wherein the material obtained by Example 5 was synthesized more uniformly and had better photochromic performance, so the conditions of Example 5 were continued to be selected to optimize the microwave power, see Examples 5, 9 and 10, the difference between the samples synthesized by different powers was reflected in the contrast before and after the sample discoloration, the material synthesized by Example 5 had better photochromic performance and higher contrast, so Example 5 was selected to optimize the subsequent amount of flux added, see Examples 5, 11 and 12, different amounts of NaCl were added to the reactants to provide a synthesis environment in the liquid phase, and by comparison, the material obtained by Example 11 reacted more uniformly, and also had better optical properties, which was more obvious in the color contrast before and after photochromism. In summary, after a series of optimizations, it was finally obtained that Example 11 was the best synthesis condition, so this synthesis strategy was selected to optimize the doping amount of Eu ions.

[0198] Optimization of Eu ion doping amount see Figure 3 , Figure 3 The standard diffraction card PDF#01-072-5905 was used as a reference to verify the synthesis of different Eu2O3 additions under the same conditions. The X-ray diffractometer was used to test and analyze the materials obtained in Examples 11 and 13-17. The results are as follows: Figure 3 As shown, the XRD data of the product is consistent with the standard diffraction card, indicating that the samples can be successfully synthesized under different europium ion doping conditions.

[0199] Furthermore, the photochromic ability of the synthesized samples was studied, e.g. Figure 4, from left to right are the photochromic photos of the materials of Examples 11 and 13-17 after irradiation with 254nm ultraviolet light. The colors after color change are all purple. It is found that except for the material of Example 13, the materials of other Examples 11 and 14-17 all have good photochromic properties. This shows that the Sr5(PO4)3F sample itself does not have the ability to change color, and the doping of Eu ions gives the sample the ability to change color under ultraviolet irradiation. Figure 5 The difference in reflectivity before and after photochromism is a comparison of the absorbance positions and photochromic intensities of Examples 11 and 13-17. Figure 5 It can be seen that the samples have changes in absorbance near 396nm and 554nm, and the Sr5(PO4)3F:1%Eu material obtained in Example 5 has the best photochromic property, so this material was selected for subsequent experiments.

[0200] Figure 6 The XRD (X-ray diffraction) standard diffraction cards of Sr5(PO4)3F and Sr5(PO4)3Cl were used as references to verify the synthesis of the samples under the same conditions under which chlorine gradually replaced fluorine. The materials obtained in Example 11 and Examples 18-22 were tested and analyzed by operating an X-ray diffractometer, and the results obtained are as follows: Figure 6 As shown, the XRD data of the product is consistent with the standard diffraction card, indicating that the samples can be successfully synthesized under different chloride ion substitutions. Figure 7 These are the UV reflectivity images of the samples obtained in Examples 11, 20 and 22 and the corresponding photochromic photographs, from left to right they are the materials when x=1, y=0, y=0.6 and y=1. It can be seen that the material has achieved a transition from purple to green and then to blue, which is specifically manifested in the change in the visible light absorbance of the material after photochromism.

[0201] Further comparison of the color center position shows the specific changes such as Figure 8 As shown, the curves from top to bottom are respectively the normalized reflectivity differences of Example 11 and Examples 18-22. Figure 8 It can be seen that the color center of the sample near 554nm is red-shifted to around 620nm, which also makes the color of the sample after photochromism change from purple to green and then to blue. Fig. 9 For the comparison of the photochromic intensity of Example 11 and Examples 18-22, by selecting the change in area before and after photochromism in the range of 300nm-800nm ​​for intensity comparison, it can be seen that the color change intensity has a trend of first decreasing and then increasing.

[0202] The microscopic morphology of the material was analyzed. Since the EDX (energy dispersive X-ray spectrometer) spectra in Examples 1-22 are similar, we selected Example 20 with the most average composition for display. Fig.10 It can be seen that the microscopic morphology of the material obtained in Example 20 photographed under a scanning electron microscope (SEM) presents a smooth morphology. In addition, the material obtained in Example 20 was tested by energy dispersive X-ray spectroscopy under a scanning electron microscope, and the mapping mode was selected. The test results are as follows: Fig.10 As shown in the figure, it can be seen that the sample in Example 20 contains six elements, namely Sr, P, O, Cl, F and Eu, and according to the different marking colors between different elements, it can be seen that the elements in the sample are evenly distributed, proving that the preparation method of the present invention is feasible and the material quality is excellent. Further, the material obtained in Example 20 was tested for cyclicity. Fig.11 This is a repeatability test picture. It can be seen that the material still maintains good photochromic ability in 10 consecutive coloring and fading cycles, indicating that the material fully meets the requirements of application and life.

[0203] See also Fig.12 , Fig.12 The materials prepared in Examples 11, 20 and 22 of the present invention are selected. The pictures are butterfly mold pictures from left to right. The materials obtained using Examples 11, 20 and 22 are filled with pictures of different parts of the butterfly and the discoloration pictures after ultraviolet light irradiation. It can be seen that the lower wings of the butterfly select the sample of Example 11, which is purple after discoloration, the material of Example 20 selected for the middle body part of the butterfly is green after discoloration, and the upper wings of the butterfly select the sample of Example 22, which is blue after discoloration. This multi-color encryption form greatly improves the security of information through different combinations of multi-colors, and meets the higher anti-counterfeiting requirements in life. In addition, the anti-counterfeiting pattern can gradually fade over time and can also be accelerated to fade with a white light flashlight, which improves its security while also showing the repeatable nature of the sample, realizing a more secure and difficult to crack multi-color anti-counterfeiting and encryption application.

[0204] In summary, the present invention uses a microwave-assisted molten salt method, uses salt as a flux, combines the microwave method with the molten salt method, and based on the high thermal stability of the molten salt and the free movement characteristics of the ions in the melt, the reactants react evenly in a liquid phase environment, and the synthesis is more uniform. Combined with the simple, fast, energy-saving and other characteristics of the microwave method, the prepared reversible photochromic apatite material with color center movement behavior, this material first gives the sample the ability to photochromic by doping Eu ions, and then gradually replaces the fluorine ions with chloride ions, realizing the change of the material color from purple to green and then to blue under ultraviolet light; the red shift of the sample color center is realized. An anti-counterfeiting label that changes color with ultraviolet light is made, which can meet most of the simple anti-counterfeiting needs and some complex pattern anti-counterfeiting needs with high requirements. Therefore, the anti-counterfeiting graphic chooses a complex butterfly pattern, which can better highlight the advantages brought by the polychromaticity of the material, not only meeting the color requirements, but also greatly improving the security and cracking difficulty. In addition, the colored patterns can fade gradually over time and can also be accelerated by long-wavelength light exposure, thereby improving their concealment. Through complex anti-counterfeiting graphics, a more secure and difficult-to-crack multi-color anti-counterfeiting and encryption application is achieved.

[0205] The present invention has been described in detail with reference to the aforementioned embodiments. For those skilled in the art, it is still possible to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A reversible photochromic apatite material with color center migration behavior, characterized in that: The chemical formula is: Sr5(PO4)3F 1-y Cl y :x%Eu, where x=0~4; y=0~1.

2. A method for preparing a reversible photochromic apatite material with color center migration behavior according to claim 1, characterized in that: The following steps are involved: Step (i), weighing reactants SrCO3, SrF2, SrCl2 and (NH4)2HPO4 according to molar percentage 9:1-y:y:6 and adding x% Eu2O3, where x ranges from 0 to 4 and y ranges from 0 to 1, to obtain a mixture and transfer it into a mortar; Step (ii), adding 0.1-1 g of a flux NaCl per 0.5 g of the mixture in a mortar, and then adding 2-6 mL of anhydrous ethanol to 0.5 g of the mixture to mix, and grinding to obtain a dry and uniformly mixed reaction mixture; Step (iii), first, prepare a microwave receiving device, the microwave receiving device is a carbon powder crucible filled with 10-20 mesh activated carbon particles, the activated carbon particles act as receivers of electromagnetic waves to generate high temperature and reducing atmosphere; then, weigh the reaction mixture obtained in step (ii), place it in a sample crucible and cover the crucible with a crucible cover, the capacity ratio of the carbon powder crucible to the sample crucible is 9:1, place the sample crucible in the microwave receiving device and ensure that the activated carbon particles evenly wrap the sample crucible; finally, place the microwave receiving device in the cavity of the aluminosilicate insulation brick with a cavity, seal both ends of the cavity with insulation bricks of equal area, and place it in a preprogrammed microwave reactor; Step (iv), setting the power of the microwave reaction furnace to 800-1000W, the time to synthesize for 15-30min, after the reaction is completed in a high-temperature reducing atmosphere, washing with alcohol and drying to obtain the reversible photochromic apatite material with color center migration behavior.

3. The method for preparing a reversible photochromic apatite material with color center migration behavior according to claim 2, characterized in that: In the step (ii), 0.5 g of the flux NaCl is added to every 0.5 g of the mixed material, and 4 ml of anhydrous ethanol is mixed with every 0.5 g of the mixed material, and a dry and uniformly mixed reaction mixture is obtained after grinding.

4. The method for preparing a reversible photochromic apatite material with color center migration behavior according to claim 2, characterized in that: In the step (iii), the mass of activated carbon particles required for every 0.5 g of reaction mixture is 11 to 15 g.

5. The method for preparing a reversible photochromic apatite material with color center migration behavior according to claim 2, characterized in that: In the step (iv), the power of the microwave reaction furnace is 1000 W and the microwave time is 25 min.

6. An application of the reversible photochromic apatite material with color center migration behavior according to claim 1, characterized in that: The apatite material is applied to anti-counterfeiting labels: the apatite material is ground to obtain a powder sample with uniform particles, and the prepared powder sample is combined with a pattern template to obtain a multi-color anti-counterfeiting label that changes color with ultraviolet light.

Citation Information

Patent Citations

  • Purple sodalite material with reversible photochromic behavior as well as preparation method and application of purple sodalite material

    CN118343775A